International negotiation in China and India a comparison of the emerging business giants - Kumar, Rajesh 1954-; Worm, Verner (Palgrave Macmillan, 2011)
Negotiation is an important managerial skill. The ability to negotiate across cultures becomes even more challenging due to differences in institutional practices.This bookexplores how the institutional environment in India and China shapes their negotiating behaviour
Keywords: Business negotiation / China / India; International business / China / India; Business and Management; Negotiation in business / China; Negotiation in business / India; Corporate culture / China; Corporate culture / India; Business etiquette / China; Business etiquette / India; National characteristics, Chinese; National characteristics, East Indian; Unternehmenskultur; Geschäftsverbindung; Indien; China